"From ear to trunk"—magnetic resonance imaging reveals referral of pain. Issue 9 (September 2018) - Forstenpointner, Julia; Wolff, Stephan; Stroman, Patrick W.; Jansen, Olav; Rehm, Stefanie; Baron, Ralf; Gierthmühlen, Janne
Abstract : Abstract: Referred and projecting pain can be observed in acute and chronic pain states. We present the case of a 69-year-old female patient with postherpetic neuralgia in dermatome Th2/3 who reported that touching the ipsilateral earlap (dermatome C2) would enhance pain and dynamic mechanical allodynia in the affected Th2/3-dermatome. The aim was to investigate possible underlying mechanisms of this phenomenon using the capsaicin experimental pain sensitization model, quantitative sensory testing, and functional spinal and supraspinal magnetic resonance imaging. The presented study provides evidence that a referral of pain from the ear to the trunk is possible. We discuss whether the observed phenomenon in combination with activation of pain-modulating areas on functional magnetic resonance imaging suggests either (1) a shift of descending pathways from inhibitory towards facilitating mode or (2) a deafferentation-induced reorganization of somatotopic maps, as the ear and the trunk are adjacent areas of the sensory homunculus. The results and a review about projection of pain in head–neck area are provided. Abstract : For the first time, evidence is presented that a referral of pain from the ear to the trunk is possible, and underlying mechanisms of this phenomenon were investigated.